Fibroblast growth factor 21 attenuates salt-sensitive hypertension-induced nephropathy through anti-inflammation and anti-oxidation mechanism - Hua-Chun Weng (BMC, 2021)
Abstract Background Patients with salt-sensitive hypertension are often accompanied with severe renal damage and accelerate to end-stage renal disease, which currently lacks effective treatment. Fibroblast growth factor 21 (FGF21) has been shown to suppress nephropathy in both type 1 and type 2 diabetes mice. Here, we aimed to investigate the therapeutic effect of FGF21 in salt-sensitive hypertension-induced nephropathy. Methods Changes of FGF21 expression in deoxycorticosterone acetate (DOCA)-salt-induced hypertensive mice were detected. The influence of FGF21 knockout in mice on DOCA-salt-induced nephropathy were determined. Recombinant human FGF21 (rhFGF21) was intraperitoneally injected into DOCA-salt-induced nephropathy mice, and then the inflammatory factors, oxidative stress levels and kidney injury-related indicators were observed. In vitro, human renal tubular epithelial cells (HK-2) were challenged by palmitate acid (PA) with or without FGF21, and then changes in inflammation and oxidative stress indicators were tested. Results We observed significant elevation in circulating levels and renal expression of FGF21 in DOCA-salt-induced hypertensive mice. We found that deletion of FGF21 in mice aggravated DOCA-salt-induced nephropathy. Supplementation with rhFGF21 reversed DOCA-salt-induced kidney injury. Mechanically, rhFGF21 induced AMPK activation in DOCA-salt-treated mice and PA-stimulated HK-2 cells, which inhibited NF-κB-regulated inflammation and Nrf2-mediated oxidative stress and thus, is important for rhFGF21 protection against DOCA-salt-induced nephropathy. Conclusion These findings indicated that rhFGF21 could be a promising pharmacological strategy for the treatment of salt-sensitive hypertension-induced nephropathy.